When two become one: How group mergers affect solidarity - Jan Schmitz (Games, 2019)
Solidarity in teamwork situations is important for the success and longevity of teams. This paper studies how helping group members is affected when groups are randomly merged and increase in size. Group mergers put social norms that are prevailing in previously small groups to the test as new team members may not share the same norms and values. I present results from an experiment in which subjects interact in groups and face the decision to help a group member who is in need of help due to an exogenous shock. Subjects interact in small groups in the first part of the experiment and groups are randomly merged to form big groups in the second part of the experiment. Helping rates are higher in merged groups compared with big groups that stay in the same constellation throughout the experiment. Moreover, in merged groups, high helping norms are more influential compared with low helping norms.
Keywords: 330; exogenous group mergers; solidarity; social preferences; social norms; experimental economics